Oral Administration of Moringa Leaf Ethanol Extract (Moringa Oleifera) for 14 Days Protects The Liver of Male White Rats (Rattus Norvegicus) from Acute Damage Caused by High Doses of Paracetamol - Syazili Mustofa; Gusti Agung Putu Yogy Veda Ananta (Sriwijaya Journal of Medicine, 2022)
Paracetamol is a widely utilized medication globally and is the primary cause of poisoning incidents in high-income countries. Paracetamol induces hepatotoxicity that is depending on the dosage when taken in excessive amounts. The Moringa oleifera (MO), belonging to the Moringaceae family, is one of the medicinal plants investigated for its potential in treating hepatotoxicity. The MO tree extracts have been documented to possess inhibitory effects, primarily against hepatitis drug-induced hepatotoxicity, owing to their bioactive components. An experimental laboratory enrolled using 36 samples of male white rats (Rattus norvegicus), which were divided into six groups: standard control group (K), positive control group (K1) given paracetamol 3000mg/kg BW on 15th days; antioxidant control group (K2) given vitamin c 500mg/kg BW for 14 days; treatment group 1 (P1), treatment group 2 (P2) and treatment group 3 (P3) each given moringa oleifera leaves extract 200mg/kg BW, 400mg/kg BW and 800mg/kg BW for 14 days. Each group, except the standard control group, was given paracetamol 3000mg/Kg BW on the 15th day. On the 16th day, the mice were euthanized, and then their livers were made into histological preparations and examined using a microscope at 40 times magnification. The level of liver cellular damage was categorized into scoring based on the level of damage. Score 1 if no damage, score 2 if parenchymatous degeneration was found, score 3 if hydropic degeneration was found, and score 4 if necrosis was found. The average scoring per group was calculated as K: 1.1; K1: 3.17; K2: 1.57; P1: 1.5; P2: 1.73; P3: 1.9. K1 appeared necrotic. Inflammation and hydropic degeneration were found in K2, P1, P2, and P3. Data were analyzed using the Kruskal-Wallis Test, obtained p = 0.000 (p < 0.05). Moringa leaf ethanol extract affected hepatic induction by paracetamol because significant differences were found between groups P1, P2, and P3 with K1 (p < 0.05). There were no significant differences between groups K2 and P1 (p > 0.05), showing that the effect of giving 500mg/kg BW vitamin C was equivalent to providing 200mg/kg BW Moringa leaves. It was concluded that giving ethanol extract of Moringa oleifera leaves protected the acute histopathological damage of the liver of male white rats of the Sprague Dawley strain induced by paracetamol.